PSYCHOLOGICAL PECULIARITIES OF CREATIVE ACTIVITY DEVELOPMENT OF FUTURE PSYCHOLOGISTS - Гоцуляк, Н. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The article is devoted to the study of the psychological peculiarities of the development of creative activity of future psychologists. Creativity as a scientific problem in psychology began to be studied relatively long ago, it is one of the most serious areas of theoretical and experimental study. A creatively active person differs not in the presence of some special, unique qualities, but mainly in the development of those that are necessary for productive activity. It is necessary to take into account that the personality is integral and therefore the predominant development of its individual features can not be accompanied by a qualitative restructuring of the entire structure. Key words: creativity, creative activity, creatively active person, mechanism of creativity, motivational factors, self-education, future psychologists.